The use of fern herbarium as a project and learning material in project-based learning to improve learning outcome - Dea Fitri Natasya; Entin Daningsih; Anisyah Yuniarti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Herbarium is a plant specimen used by experts to identify plants; however, it can also be used as teaching concept. Skill and knowledge are needed in making herbarium to produce standard herbarium giving good description and easy for identification. Unfortunetely, herbarium project is rarely used to improve skill and plant identifications knowledge for students. This study aimed to determine the skills of students in making herbarium and training students to identify plants through the PjBL model. In addition, this study aimed to compare the learning outcomes of students making herbarium taught with the PjBL model (experimental class) with the Direct Instructions model (control class). The method was quasi experiment with Nonequivalent Control Group Design. Instruments were test questions and learning tools such as teaching modules, student worksheet, herbarium, and assessment sheets for the evaluation students' attitudes and skills that have been validated by 2 validators using the Guttman scale. Identification of herbarium made by experimental class students referred to standard herbarium of research results in Hutan Lindung Gunung Raya, as learning material, while the control class used literature such as internet. Implementation of learning was in accordance to the stages PJBL or DI. Herbarium made by experimental class students was more accurate in identification and description compared to those of control class herbarium. PjBL also improved student cognitive, psychomotor, and affective significantly. This indicates that the use of other environment-based projects can be developed in PjBL and provides more opportunities for students to explore ways out of a problem.  Abstrak. Herbarium adalah spesimen tumbuhan yang digunakan oleh para ahli untuk mengidentifikasi tumbuhan; tetapi juga dapat digunakan sebagai konsep pembelajaran.  Keterampilan dan pengetahuan dibutuhkan dalam pembuatan herbarium untuk menghasilkan herbarium standar yang memberikan deskripsi yang baik dan mudah diidentifikasi. Syangnya, proyek herbarium jarang digunakan untuk meningkatkan keterampilan dan pengetahuan identifikasi bagi peserta didik. Studi ini bertujuan untuk mengetahui keterampilan peserta didik dalam membuat herbarium dan melatih peserta didik untuk mengidentifikasi tumbuhan melalui model PjBL. Selain itu, studi ini bertujuan membandingkan hasil belajar peserta didik diajar dengan model PjBL (kelas eksperimen) dengan model Direct Instructions (kelas kontrol). Metode yang digunakan adalah kuasi eksperimen dengan Nonequivalent Control Group Design. Instrumen adalah soal tes dan perangkat pembelajaran seperti modul ajar, lembar kerja peserta didik, herbarium, dan lembar penilaian untuk evaluasi sikap dan keterampilan peserta didik yang sudah divalidasi oleh 2 orang validator menggunakan skala Guttman. Identifikasi herbarium yang dibuat oleh peserta didik kelas eksperimen mengacu herbarium standar hasil dari penelitian di Hutan Lindung Gunung Raya, sebagai bahan ajar, sementara pada kelas kontrol peserta didik mengacu literatur seperti internet. Implementasi pembelajaran dilakukan sesuai dengan sintaks PJBL atau DI. Herbarium yang dibuat oleh peserta didik pada kelas eksperimen lebih akurat dalam identifikasi dan deskripsi dibandingkan dengan herbarium dari kelas kontrol. PjBL juga meningkatkan pengetahuan, keterampilan, dan sikap peserta didik secara signifikan.  Ini mengindikasikan bahwa penggunaan proyek lain berbasis lingkungan dapat dikembangkan dalam PJBL dan memberikan kesempatan lebih banyak kepada peserta didik menggali jalan keluar dari sebuah masalah.